Efektivitas Penggunaan Media Pembelajaran Dakonmatika untuk Meningkatkan Kemampuan Berhitung Siswa Kelas IV SDN Kalanganyar Sedati Sidoarjo - Ardianik Ardianik; Umar Hadi (Universitas Kanjuruhan Malang, 2022)
The purpose of this study was to test and prove the difference in numeracy skills before and after using Dakonmatics learning. With a quantitative research approach and the type of pre-experimental research, namely One Group Pretest – Posttest (before and after). The research sample was the fourth grade students of SDN Kalanganyar Sedati Sidoarjo for the academic year 2021/2022, which amounted to 31 students. Data collection used the test method. T-test to test the effectiveness of using dakonmatics learning media. The results showed that there was a very significant difference in numeracy skills before and after using the dakonmatics learning media, this is evidenced by the magnitude of the probability (Sig. 2-tailed) = 0.000 < α = 0.05 and even more smaller than α = 0.01. So it can be concluded that the use of Dakonmatika learning media is effective in improving numeracy skills in FPB and KPK materials.